Assessment of Fetal Cardiac Function by Tissue Doppler Technique in Normal Fetuses of Cairo governorate - Abdel R.M. Maher; Mohammed A.S. Mohammed Ahmed; Mahmoud I. El-Rashidy (Al-Azhar Assiut Medical Journal)
Background and aim The effectiveness of tissue Doppler imaging has been outlined in recent studies. This study aims to establish adjusted reference ranges and study the influence of gestational age (GA) and estimated fetal weight (EFW) on tissue Doppler cardiac function measures. Patients and methods This was a cross-sectional study. The study included 385 healthy pregnancies between the GAs of 18 and 42 weeks who were getting ultrasound scan between May 2019 and May 2021. The inclusion criteria were singleton pregnancy without fetal malformations and healthy pregnant women, and those with established medical issues or pregnancy complications were excluded. Results The Mean±SD right myocardial performance index (Rt MPI) was 0.46±0.093 for 18–42 weeks of gestation. The Rt MPI seems to be slightly decreased with GA and EFW. The Rt MPI had no correlation with maternal age, BMI, or parity, with P values of 0.5, 0.6, and 0.2, respectively. Median Rt MPI was found to be relatively constant and had a slight decrease from 18 to 42 weeks of gestation. Conclusion Fetal Rt MPI remains stable and slightly decreased against GA in second and third trimesters. It may create EFW and GA-adjusted reference range foundation for future investigations.